1988
DOI: 10.1002/ijc.2910420506
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐barr virus‐positive recipient type B‐cells survive in a “complete chimera” after allogeneic bone‐marrow transplantation

Abstract: Yao et al., 1985a) or of survival of low numbers of infected B cells (Yao et al., 198%). Lymphoproliferative tumors do not usually carry EBV genomes (Andiman et al., 1983) but a few cases of EBV-positive lymphoma have been described following BMT (Schubach et al., 1985). These were monoclonal (Schubach et al., 1982), but polyclonal tumors have been described as well and all were of donor origin whenever this point was investigated (Martin et al., 1984). This, together with the observation that EBV-specific cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A large number of studies suggested the B lymphocyte as the most likely site of EBV persistence (as well as primary infection), 13‐16 consistent with the high density of EBV receptors (CD 21) and virus‐triggered transformation pathways in these cells 17‐21 . Other studies, however, suggest that mucosal epithelium in oropharyngeal or other sites 22‐24 may be the target of primary EBV infection and the site of EBV persistence.…”
Section: Introductionmentioning
confidence: 89%
“…A large number of studies suggested the B lymphocyte as the most likely site of EBV persistence (as well as primary infection), 13‐16 consistent with the high density of EBV receptors (CD 21) and virus‐triggered transformation pathways in these cells 17‐21 . Other studies, however, suggest that mucosal epithelium in oropharyngeal or other sites 22‐24 may be the target of primary EBV infection and the site of EBV persistence.…”
Section: Introductionmentioning
confidence: 89%